Improving Metacognitive Ability and Learning Outcomes with Problem-Based Revised Bloom's Taxonomy Oriented Learning Activities - I Gusti Agung Lanang Parwata; I Nyoman Laba Jayanta; I Wayan Widiana (Emerging Science Journal, 2023)
This study aims to analyze the impact of Bloom's revised taxonomy-oriented learning activities with problem-based learning models on students' metacognitive skills and learning outcomes. A quasi-experimental design is used as the research method, and the quasi-experimental design is implemented as a pure post-test-control design. All fourth-year students participated in the study, with a total of 132 students participating. The sample was randomly selected and corresponded to 84 students. A 10-question test was used to collect the data. MANOVA with SPSS support was used as the analytical method. The significance of the test results was < 0.00. According to the results, 0.05. This means that learning that uses a combination of problem-based learning models and learning activities aligned with the revised Bloom taxonomy can influence students' metacognitive skills and learning outcomes. Students are at the central of their learning, so they are actively involved in the learning process. This learning activity develops students' metacognitive skills and provides an opportunity to reflect on what they know about themselves and to be honest and confident in their knowledge. Additionally, learning activities are organized by learning objectives to help students improve their learning outcomes. Doi: 10.28991/ESJ-2023-07-02-019 Full Text: PDF